Doping SrSnO3 Perovskite with Transition Metals: Synthesis of Double Hydroxides, Thermal Decomposition, and Pigment Potential - Dohnalová, Žaneta; Hroch, Jan; Reinders, Nataliia; Luxová, Jana; Šulcová, Petra (Elsevier Science BV, 2024)
The primary objective of this research is to explore the feasibility of synthesizing phase-pure perovskite SrSnO3 doped with transition metals and to evaluate the potential of these products as high-temperature inorganic pigments. The initial step in preparing perovskite powders with the general formula SrSn0.95M0.05O3-δ (M = Mn, Fe, Co, Ni) involved synthesizing SrSn0.95M0.05(OH)6 followed by its thermal decomposition. The thermal decomposition processes and the reaction pathway for perovskite formation were analyzed using thermal analysis and X-ray diffraction analysis. Single-phase products of beige SrSn0.95Fe0.05O3-δ and brown SrSn0.95Co0.05O3-δ were successfully obtained by calcining the precursors at 1 100 °C. In contrast, brown SrSn0.95Mn0.05O3-δ contained a phase impurity of SnO2 and doping with Ni ions resulted in a phase mixture of SrSnO3 and NiO. The pigment quality of the powders was assessed based on their color parameters, described using the CIE Lab system.
Dopování perovskitu SrSnO3 přechodnými kovy: Syntéza podvojných hydroxidů, tepelný rozklad a pigmentový potenciál
Keywords: Hydroxystannate; SrSnO3; Thermal decomposition; Coprecipitation; Perovskite pigment; hydroxystanát; SrSnO3; termický rozklad; srážení; perovskitový pigment